Implementasi Konsep Tri Hita Karana (THK) Dalam Pengelolaan Keuangan Desa Adat Selat Pandan Banten - Santosa, Made Satria Wira Adi; Darmawan, Nyoman Ari Surya (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to understand how the implementation of the Tri Hita Karana (THK) concept in financial management of the Pandan Strait Village of Banten. This research was conducted in the Adat Selat Pandan Banten Village, Sukasada District, Buleleng Regency, Bali. This research uses qualitative research methods and this type of research is descriptive qualitative. The data sources of this research are primary data and secondary data. Data collection in this study was carried out through interviews, observation and documentation. The data analysis technique used in this research is data collection, data reduction, data presentation, and conclusion confirmation. The result of this research is that the Pandan Strait Village of Banten is guided by the concept of Tri Hita Karana (THK), it has been regulated in awig-awig Desa Adat Selat Pandan Banten. To carry out its activities, the Strait of Pandan Banten Traditional Village needs funds allocated for 3 ways, namely Parahyangan Pawongan and Palemahan. The financial management process of the Desa Adat Selat Pandan Banten consists of 4 stages, namely planning, budgeting, implementation, reporting and accountability and accountability which have been carried out in a transparent and accountable manner.Â